The Parliamentary Dimension of North Macedonia’s Accession to the European Union - Isabelle Ioannides, Ivan Damjanovski and Zoran Nechev (Konrad Adenauer Foundation in the Republic of North Macedonia/Institute for Democracy Societas Civilis Skopje, 2019)
The brief analyses the new dynamics in the new EU legislature on EU enlargement to the Western Balkans, its impact on the EU’s perspective to North Macedonia, and the role of the Assembly of North Macedonia in pushing for the country’s European perspective.